3(1-x)=2x-6(6x+3)

Simple and best practice solution for 3(1-x)=2x-6(6x+3) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(1-x)=2x-6(6x+3) equation:



3(1-x)=2x-6(6x+3)
We move all terms to the left:
3(1-x)-(2x-6(6x+3))=0
We add all the numbers together, and all the variables
3(-1x+1)-(2x-6(6x+3))=0
We multiply parentheses
-3x-(2x-6(6x+3))+3=0
We calculate terms in parentheses: -(2x-6(6x+3)), so:
2x-6(6x+3)
We multiply parentheses
2x-36x-18
We add all the numbers together, and all the variables
-34x-18
Back to the equation:
-(-34x-18)
We get rid of parentheses
-3x+34x+18+3=0
We add all the numbers together, and all the variables
31x+21=0
We move all terms containing x to the left, all other terms to the right
31x=-21
x=-21/31
x=-21/31

See similar equations:

| -x2-x+30=0 | | 15+10x4=Y | | 35t+5=180 | | -x2-11x-28=0 | | 2(x+3)=x+16# | | 1-7(4x-1)=6(-2x-3)-4 | | W^2-2w=120 | | P=2x19+2x99 | | x*0.2=560 | | 0,5z-4=12 | | 36/b=3 | | 73x2-81x=0 | | 27x2+23x=0 | | 8j=48 | | x2+85x=0 | | (y+23=) | | x÷4+5=8 | | -x2+13x=0 | | 16x2+x=0 | | -2-13.4x=-8x-(6x+1) | | 17y-2(6y+1)=8 | | 2x+125=180 | | x÷5+5=3+x | | x/90^2=0.1 | | 1,5y+4=10 | | (11x+16)+(12x+7)=180 | | 30=14x-47 | | 3z/7-6=-5 | | .6x^+.35=19 | | 11x+16=180 | | 0.08x+17.95=0.09x+16.05 | | 0=2(-7)+b |

Equations solver categories